Reklama internetowa w promocji ruchu turystycznego na wsi - Jan Sikora; Agnieszka Wartecka-Ważyńska (Ekonomiczne Problemy Turystyki, 2016)
With growing popularity of the Internet, online advertising is becoming a popular source of information about rural tourism. This helps effectively provide commercial information for various groups of consumers. The aim of the paper is to illustrate the importance of online advertising to development of tourist movement in rural areas. It was demonstrated that online advertising represents an essential source of transfer and acquisition of information about rural tourism, and, that the system of online advertising in the area of rural tourism is more efficient than the advertising used by tourist entities in rural areas. The paper was written based on the literature review, analysis of the quantitative data obtained from secondary materials and results of empirical studies published in research reviews.